(untitled) - Byrne, Jo-Ann C. (San Francisco, CA., 2006)
Byrne and Rees share their direct experience to provide a highly practical guide for organizations seeking more self-managed approaches to learning in leadership development programs. It will stimulate and encourage all concerned who ask how they can better align the learning needs of individual leaders with those of their organization.
Keywords: Leadership,Performance standards,Người điều hành,Lãnh đạo,Tiêu chuẩn thực hiên,Executives; Study and teaching,Đào tạo,Học tập và nghiên cứu,Training of